Life, decay and fossilisation of endolithic microorganisms from the Ross Desert, Antarctica - Wierzchos, Jacek; Ascaso, Carmen (Polar Biology, 2001)
6 pages, figures, and tables statistics. The adaptation and survival of the endolithic microrganisms that colonise the near-surface layer of porous sandstone rock in the Ross Desert (Antarctica) depend upon a precarious equilibrium of biological, geological and climatic factors. Peer reviewed